Lateral Rectus Muscle Expands More Than Medial Rectus Following Maximal Deep Balanced Orbital Decompression. Issue 2 (March 2018) - Gupta, Adit; Nobori, Alex; Wang, Yi; Rootman, Daniel; Goldberg, Robert
Abstract : Purpose: It has been reported that extraocular muscles can enlarge following orbital decompression in thyroid eye disease. In this article, the authors studied the changes in extraocular muscles size following maximal deep lateral and medial balanced decompression in a large sample of thyroid eye disease patients. Methods: Imaging data were reviewed preoperatively and postoperatively. Radiologic proptosis was assessed. Maximal axial muscle width of the medial and lateral recti was measured. Results: Data from 48 consecutive patients (75 orbits) were included. There was a significant increase in the width of both the lateral and medial recti after decompression ( p < 0.01). The mean (standard deviation [SD]) change was less for the medial rectus (0.7 mm) than for the lateral (2.7 mm). This difference was significant ( p < 0.01). For the lateral rectus, 80% of all decompression surgeries were associated with an increase in width of >1 mm. Mean (SD) proptosis reduction was 8.2 mm (3.4 mm). Conclusion: These results suggest that the extraocular muscles enlarge in the most deep lateral wall decompressions. For decompression as performed in this article, expansion tends to be more commonly found and of a greater magnitude in the lateral rectus compared with medial. Abstract : The study demonstrated that both the medial and lateral recti expand in width significantly after balanced deep lateral and medial decompression in thyroid eye disease.